Development of CMV‐specific cytotoxic T cells (CMV‐Tc) in pediatric renal transplant recipients with CMV viremia. (14th August 2021) - Pizzo, Helen; Shin, Bongha; Garrison, Jon; Huang, Edmund; Malekzadeh, Mohammad; Jordan, Stanley C.; Puliyanda, Dechu; Toyoda, Mieko
Abstract: Background: Viral infections are controlled primarily by viral‐specific T cells, raising concern for adequate T‐cell response to clear CMV infection in transplant recipients receiving lymphocyte‐depleting agents (LDA). We examined the rates of CMV viremia and clearance, seroconversion, and CMV‐specific CD8+ T cell (CMV‐Tc) activity with class of induction agent received. Methods: Retrospective review of 45 pediatric renal transplant recipients who received induction with LDA ( n = 31) or non‐LDA (NLDA; n = 14) received valganciclovir prophylaxis for 6 months post‐transplant and CMV‐PCR monitoring. CMV‐Tc was measured by intracellular IFNγ flow cytometry, when possible, at baseline, 1 month after CMV viremia (>5 copies/PCR) and serially until CMV‐Tc was positive (≥0.2%). Results: Viremia rates at 1, 2, and 4 years post‐transplant were higher in LDA vs. NLDA (46.3% vs. 7.2%, 64.2% vs. 7.2%, and 64.2% vs. 7.2%, respectively; p = .002). Viremia rates at these time points in seronegative LDA (50.3%, 71.6%, 71.6%) were significantly or near significantly higher than seronegative NLDA (9.1%, 9.1%, 9.1%; p = .004), seropositive‐LDA (22.3%, 22.3%, 22.3%; p = .07), or seropositive NLDA (0%, 0%, 0%; p = .07). Eleven of 17 (64.7%) viremic subjects required valganciclovir dose reduction during the prophylaxis period for leukopenia. All viremic LDA patients developed CMV‐Tc. One viremic NLDA patient did not develop CMV‐Tc. No patients developed CMV disease. Conclusion: CMV seronegative pediatric renal transplant patients receiving LDA are more likely to have valganciclovir prophylaxis dose reduction and develop subclinical CMV viremia; however, all developed CMV‐Tc. Larger prospective studies are needed to further understand the effects of induction agents on CMV‐Tc and CMV‐Tc's role post‐transplant.